MODELLING AND ANALYSIS OF PVSC TYPE BUCK BUCK-BOOST DC-DC CONVERTER - T Ram Manohar Reddy; Shaik Hussain Vali; Phanindra Thota; Kamaraju Kamaraju (Proceeding of International Conference on Information Science and Technology Innovation (ICoSTEC), 2022)
In the era of modern industrial development, power electronics equipment has been developed aggressively and brought dc system again in power utilization to use clean energy resources like solar array, fuel cell, wind generator, etc. Since the past decade, power electronics equipment has become very popular; hence, the switch-mode converter requirement is increasing rapidly day by day in applications like communication power supply, space crafts, hybrid electric vehicles, micro-grid and nano-grids. Among the various available configurations of converters, Multi-Input DC/DC converters became more and more popular in power electronics field, especially, for provide interface of various renewable energy sources and deliver regulated power to several loads. In this article, a PVSC type Buck Buck-Boost Dual-Input DC- DC Converter (DIDC) is designed and modelled for DC grid application. The proposed converter is driven with two renewable energy sources PV cell and a battery having different amplitudes which can able to deliver the power from source to load individually or simultaneously. DIDC tropology is simply configured with two passive elements L, C, diodes D1 D2 and switches S1, S2. The Dual-Input DC-DC Converter suitability is validated by carrying out simulations in different modes of operation. The de-centralized PID controller is designed for voltage and current loop controller to ensure the DC output voltage of 48 V, load current of 4.8 A and power of 230W. The Stability of the closed-loop converter is also verified under all possible source and load disturbance conditions. The simulations and analysis of the proposed converter are carried out using MATLAB and PSIM software